Determination of the appropriate level of manure fertilisation for Moringa oleifera grown for animal feed - Tran Thi Hoan; Tu Quang Hien; Mai Anh Khoa; Tu Quang Trung (Vietnam Journal of Science, Technology and Engineering, 2021)
The purpose of this study is to determine the appropriate level of chicken manure for the green fodder M. oleifera grown for leaf meal production as a supplement into poultry diet to improve poultry product quality (i.e., meat and egg). The experiment was conducted at Thai Nguyen University of Agriculture and Forestry, Vietnam, for two years from 2018 to 2019. The experiment consisted of four treatments (NT) represented by four different levels of chicken manure, namely, 0 tons (NT1), 10 tons (NT2), 20 tons (NT3) and 30 tons/ha/yr (NT4). Each treatment was carried out over an area of 24 m2 with 5 replicates. The experiment was the complete randomised block design. Other factors such as plantation density, nitrogen, phosphate, potassium fertiliser levels, cutting height, and cutting intervals, etc., were similar among treatments. The results showed that the leaf dry matter yield of NT1 through NT4 was 6.919, 8.131, 8.975, and 9.494 tons/ha/yr, respectively. That of the leaf crude protein was 2.244, 2.694, 3.073, and 3.357 tons/ha/yr, respectively. Increasing manure levels from 0 to 30 tons/ha/yr decreased the dry matter content in the leaves by 1.43%, increased the crude protein in leaf dry matter basic by 2.93%, and decreased crude fibre in the leaf dry matter basic by 2.24%. Based on these results and data from statistical analysis, the most appropriate level of chicken manure application for M. oleifera was at 20 tons/ha/yr.